Motivation and Workload Affect the Performance of Marketing and Production Employees PT. Rajawali Citramass - Anggraini, Ersa Falevi; Adiwaty, Mei Retno (PT FORMOSA CENDEKIA GLOBAL, 2025)
Human resources are a crucial component in a company. The existence of human resources can impact or influence the success of the company. This study aims to analyze the impact of work motivation and workload on employee performance in the marketing and production departments at PT Rajawali Citramass. A quantitative approach was applied in this study. The population of this study includes all employees of the marketing and production department at PT Rajawali Citramass as many as 60 people. The sampling technique applied is the saturated sampling method. The data analysis method used in this research is SmartPLS (Partial Least Square). The results of this study reveal that work motivation and workload load significantly positively on employee performance.